2023
DOI: 10.11604/pamj.2023.45.98.37017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of virological failure in pediatric patients on HAART in sub-Saharan Africa: a systematic review and meta-analysis

Nchimunya Machila,
Liyali Libonda,
Paul Habineza
et al.

Abstract: Antiretroviral treatment failure has emerged as a challenge in the management of pediatric human immunodeficiency virus (HIV) patients, especially in resource-limited countries despite accessibility to Highly Active Antiretroviral Therapy (HAART). A systematic review and meta-analysis was conducted to synthesize virological failure (VF) prevalence and ascertain its predictors in children in sub-Saharan Africa. An electronic database search strategy was conducted from January to September 2021 on PubMed, EMBASE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
0
1
Order By: Relevance
“…The incidence density of virologic failure in our cohort was 4.3 per 100 person-years, including both ART-naïve and ART-experienced children. This rate is notably lower than what has been reported in recent literature, particularly in sub-Saharan Africa, where a systematic review and meta-analysis indicated a virological failure rate of 29% (23), and a retrospective study in South Africa documented a failure rate of 18.7 per 100 person-years (24).…”
Section: Discussioncontrasting
confidence: 58%
“…The incidence density of virologic failure in our cohort was 4.3 per 100 person-years, including both ART-naïve and ART-experienced children. This rate is notably lower than what has been reported in recent literature, particularly in sub-Saharan Africa, where a systematic review and meta-analysis indicated a virological failure rate of 29% (23), and a retrospective study in South Africa documented a failure rate of 18.7 per 100 person-years (24).…”
Section: Discussioncontrasting
confidence: 58%